Classification of the glyphosate target enzyme (5-enolpyruvylshikimate-3-phosphate synthase) for assessing sensitivity of organisms to the herbicide - Leino, Lyydia; Tall, Tuomas; Helander, Marjo; Saloniemi, Irma; Saikkonen, Kari; Ruuskanen, Suvi; Puigbò, Pere (Journal of hazardous materials, 2021)
Glyphosate is the most common broad-spectrum herbicide. It targets the key enzyme of the shikimate pathway, 5-enolpyruvylshikimate-3-phosphate synthase (EPSPS), which synthesizes three essential aromatic amino acids (phenylalanine, tyrosine and tryptophan) in plants. Because the shikimate pathway is also found in many prokaryotes and fungi, the widespread use of glyphosate may have unsuspected impacts on the diversity and composition of microbial communities, including the human gut microbiome. Here, we introduce the first bioinformatics method to assess the potential sensitivity of organisms to glyphosate based on the type of EPSPS enzyme. We have precomputed a dataset of EPSPS sequences from thousands of species that will be an invaluable resource to advancing the research field. This novel methodology can classify sequences from nearly 90% of eukaryotes and >80% of prokaryotes. A conservative estimate from our results shows that 54% of species in the core human gut microbiome are sensitive to glyphosate. [Display omitted] •We classify the target enzyme of the most common broad-spectrum herbicide.•The EPSPS enzyme can be classified in sensitive or resistant to glyphosate.•We introduce the first bioinformatics method to assess potential sensitivity to glyphosate.•Glyphosate may have an impact on half of the species in the core human gut microbiome.